1999
DOI: 10.1136/emj.16.6.400
|View full text |Cite
|
Sign up to set email alerts
|

Markers for domestic violence in women.

Abstract: Objective-To determine injury patterns and characteristics specific to domestic violence in women who present to the accident and emergency (A&E) department. Design-A retrospective case note review of all female assaults over a one year period. The subjects were women who disclosed that their injuries were due to assaults by either a current or a previous male partner. Identification of markers would be important in alerting clinicians to the possibility of domestic violence, as it is known that many cases are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 18 publications
1
28
1
4
Order By: Relevance
“…Another important difference concerns the incidence of fractures. Although described as a fairly common injury [22,28], no facial fractures were found in this study; Bach et al [22] found facial fractures in 30% of DV victims, but Saddki et al [24], however, described results similar to ours, stating that there were no reported fractures, and only one case of joint dislocation.…”
Section: Discussioncontrasting
confidence: 54%
“…Another important difference concerns the incidence of fractures. Although described as a fairly common injury [22,28], no facial fractures were found in this study; Bach et al [22] found facial fractures in 30% of DV victims, but Saddki et al [24], however, described results similar to ours, stating that there were no reported fractures, and only one case of joint dislocation.…”
Section: Discussioncontrasting
confidence: 54%
“…30,31 This study also demonstrated a wide range of injuries and patterns of injuries, the majority being scratches and bruising to the head and arms which compares to other cited reports from within Northern Ireland. [32][33][34] McWilliams and Spence, in a study on the civil and criminal justice response to domestic violence in Northern Ireland, quoted that on average one woman is seriously assaulted with AOABH, GBH, or attempted murder by her male partner every day. 35 This may reflect the stronger force of male aggressors on female victims and therefore the occurrence of more serious injuries.…”
Section: %mentioning
confidence: 99%
“…Også i Norge er det funnet forbindelser mellom seksuell vold og alvorlig vold, for eksempel vold mot en gravid mage (14). Sammenhenger mellom ulike former for partnervold mot kvinner og helseproblemer er etter hvert grundig dokumentert, både nasjonalt og internasjonalt (4,(7)(8)(9)(10)(11)15).…”
Section: Seksuell Voldunclassified
“…Signifikante markører for partnervold er akutte skader i hodet, nakken og ansiktet hos kvinner som oppsøker legevakt eller akuttmottak, som angir at ingen var vitner til skaden (11). Eksempler på seksuell vold i ekteskap eller samboerforhold som avdekkes blant kvinner utsatt for partnervold, er å bli tvunget til vaginalt eller analt samleie, slått eller brent under samleie, påført objekter i vagina og anus, eller i sjeldne tilfeller tvunget til sex med andre, også dyr (12).…”
unclassified